Drug induced linear IgA dermatosis - Benedičič, Ana (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
A significant number of reports incriminate various drugs, especially vancomycin and amiodarone of provoking bullous linear IgA dermatosis. This entity also includes the subset of IgA-mediated epidermolysis bullosa acquisita. We report on a patient with histopathologically and immunologicallyproven bullous linear IgA dermatosis, who developed this condition during treatment for hypertension with enalapril. Treatment with lowdoses of dapsone, 25 mg daily, was efficient. There is strong evidence thatthe condition was triggered by enalapril.
Keywords: Aged; Dapson; Dapsone; dermatologija; drug; Drug Hypersensitivity; Enalapril; Epidermoliza bulozna, pridobljena; Epidermolysis Bullosa Acquisita; Iga; kožne bolezni; Starostniki; Therapeutic Use; zdravila; Zdravila, preobčutljivost